The effect of crop residues, cover crops, manures and nitrogen fertilization on soil organic carbon changes in agroecosystems: a synthesis of reviews - Bolinder, Martin A.; Crotty, Felicity; Elsen, Annemie; Frac, Magdalena; Kismányoky, Tamás; Lipiec, Jerzy; Tits, Mia; Tóth, Zoltán; Kätterer, Thomas (Mitigation and adaptation strategies for global change, 2020)
International initiatives are emphasizing the capture of atmospheric CO 2 in soil organic C (SOC) to reduce the climatic footprint from agroecosystems. One approach to quantify the contribution of management practices towards that goal is through analysis of long-term experiments (LTEs). Our objectives were to analyze knowledge gained in literature reviews on SOC changes in LTEs, to evaluate the results regarding interactions with pedo-climatological factors, and to discuss disparities among reviews in data selection criteria. We summarized mean response ratios (RRs) and stock change rate (SCR) effect size indices from twenty reviews using paired comparisons ( N ). The highest RRs were found with manure applications (30%, N = 418), followed by aboveground crop residue retention and the use of cover crops (9–10%, N = 995 and 129), while the effect of nitrogen fertilization was lowest (6%, N = 846). SCR for nitrogen fertilization exceeded that for aboveground crop residue retention (233 versus 117 kg C ha −1 year −1 , N = 183 and 279) and was highest for manure applications and cover crops (409 and 331 kg C ha −1 year −1 , N = 217 and 176). When data allows, we recommend calculating both RR and SCR because it improves the interpretation. Our synthesis shows that results are not always consistent among reviews and that interaction with texture and climate remain inconclusive. Selection criteria for study durations are highly variable, resulting in irregular conclusions for the effect of time on changes in SOC. We also discuss the relationships of SOC changes with yield and cropping systems, as well as conceptual problems when scaling-up results obtained from field studies to regional levels.